A method for preparing nylon-spandex fabric with high waterproof performance
By using a laminated composite technology of fluorine-containing double-flat pyrophenol intermediate with polyurethane and TPU hot melt adhesive in nystam fabrics, combined with polyester woven fabrics, the problem that fabrics in the prior art are difficult to achieve high waterproof and antibacterial at the same time. Achieve efficient compound function improvement.
Patent Information
- Application Number
- CN202411204536.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The prior art is difficult to achieve high waterproofing and antibacterial properties in jinmin fabrics at the same time, and there are fewer types of composite functions, which limits the application range of fabrics.
The fluorine-containing double pyrophene intermediate is laminated and composited with polyurethane and TPU hot melt adhesive, combined with polyester woven fabric, and prepared a chrysanthemum fabric with high waterproof performance, and the antibacterial effect of the fabric is enhanced by the antibacterial monomer of pyrophene. .
The high waterproof performance and antibacterial properties of Jinmin fabrics have been improved, the application range of fabrics has been expanded, and the hydrophobicity and antibacterial effects of the fabrics have been improved through lamination composite technology.
Smart Images

Figure CN118721813B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a method for preparing a nylon-spandex fabric with high waterproof performance. Background Art
[0002] Nylon has excellent properties such as soft feel, good elasticity, and wear resistance. Blending it with other fibers can improve the wear resistance of the fabric and improve the dimensional stability of the fabric. The molecular structure of spandex is composed of alternating soft and hard segments, and has excellent tensile and recovery properties. Blending nylon with spandex can produce nylon-spandex fabrics. Nylon-spandex fabrics are widely used in high-end sports products, with the characteristics of smooth surface, soft feel and elasticity.
[0003] With the rapid development of science and technology, especially the development of cutting-edge science and technology, higher and more requirements are put forward for the performance of textiles. The functions of fabrics are generally antibacterial, quick-drying, etc., but there are fewer types of composite functions. Therefore, preparing a nylon-spandex fabric with composite functions is conducive to expanding the application range of nylon-spandex fabrics.
[0004] Hinokitiol, also known as hinokitiol, is a natural compound containing a tropone structure. It has excellent inhibitory effects on bacteria, fungi and insects, but is non-toxic to human endothelial cells and epithelial cells. Therefore, it is widely used in medicine, agriculture, cosmetics, textiles and other fields.
[0005] For example, the patent application publication number CN113584884A discloses an antibacterial functional fabric and a preparation method thereof. Chitosan, hinokitiol, etc. are used as raw materials to prepare an antibacterial liquid, which is then coated on the fabric. The prepared fabric has a good antibacterial effect, but does not improve its waterproof effect. Summary of the invention
[0006] 1. Technical issues to be resolved
[0007] In view of the deficiencies in the prior art, the present invention provides a method for preparing a nylon-spandex fabric with high waterproof performance. The prepared nylon-spandex fabric has good waterproof performance and antibacterial performance.
[0008] (II) Technical solution
[0009] A method for preparing a nylon-spandex fabric with high waterproof performance, the preparation method is as follows:
[0010] Step (1), adding polyurethane and fluorinated bishinkalin intermediate to N,N-dimethylformamide solvent, stirring and dissolving at room temperature to obtain a casting solution, vacuum degassing, scraping on a dry and clean glass plate to form a coating film, immersing in deionized water, soaking for 48-72 hours, taking out, washing with deionized water, and drying to obtain a modified polyurethane film. The preparation method of the fluorinated bishinkalin intermediate is:
[0011] S1, adding 5-chloro-metaphenylenediamine to an ethanol solvent, stirring and dispersing, then adding formaldehyde and cypress phenol, heating to 80-95°C, reacting for 2-6 hours, and after the reaction, rotary evaporation, washing with deionized water, drying, and purification to obtain intermediate 1;
[0012] S2, adding intermediate 1 and bis(2-chloroethyl)amine to an ethanol solvent, stirring and dispersing, and then adding 70wt%-80wt% of a sodium hydroxide aqueous solution thereto, reacting at 85-95°C for 8-12h. After the reaction is completed, filtering, washing with deionized water, drying, and purifying to obtain intermediate 2;
[0013] S3, adding intermediate 2, tridecafluorooctanol, and a phase transfer catalyst to N,N-dimethylformamide solvent, stirring and dispersing, adding 70wt%-80wt% sodium hydroxide aqueous solution thereto, reacting at 40-55°C for 20-30h, after the reaction is completed, cooling to room temperature, filtering, standing, taking the organic layer, washing with saturated brine, drying, and distilling under reduced pressure to obtain a fluorinated bishinkalin intermediate;
[0014] Step (2), arranging the nylon-spandex single-sided fabric on a steel plate, placing a thermoplastic polyurethane elastomer (TPU) hot melt adhesive in a steel sieve, and evenly sprinkling the TPU hot melt adhesive on the surface of the nylon-spandex single-sided fabric through the steel sieve, and then placing a modified polyurethane film on the surface of the nylon-spandex single-sided fabric, and evenly sprinkling the TPU hot melt adhesive on the surface of the modified polyurethane film through the steel sieve, and then arranging the polyester woven on the surface of the modified polyurethane film, and finally covering another steel plate, placing it in a flat vulcanizer, and performing lamination to obtain a nylon-spandex fabric with high waterproof performance.
[0015] Preferably, in step (1), the mass ratio of polyurethane to fluorinated bishinokitiol intermediate is 100:5-25.
[0016] Preferably, in step (1), the coating thickness is 0.2-0.4 mm.
[0017] Preferably, in step (2), the amount of TPU hot melt adhesive used is 20 g / m 2 .
[0018] Preferably, in step (2), the temperature of the plate vulcanizing press is 80° C. and the pressure is 5 MPa.
[0019] Preferably, in S1, the molar ratio of 5-chloro-meta-phenylenediamine, formaldehyde and cypress phenol is 1:2.5-4:2-3.
[0020] Preferably, in S2, the molar ratio of intermediate 1 to bis(2-chloroethyl)amine is 1:1-1.5.
[0021] Preferably, in S3, the molar ratio of the intermediate 2 to tridecafluorooctanol is 1:2-2.5.
[0022] 3. Beneficial technical effects
[0023] The present invention uses 5-chloro-metaphenylenediamine, formaldehyde and cypress phenol as raw materials, obtains intermediate 1 through Mannich reaction, uses intermediate 1 and bis(2-chloroethyl)amine to undergo substitution reaction to obtain intermediate 2, and under the catalysis of a phase transfer catalyst, performs substitution reaction on intermediate 2 and tridecafluorooctanol to obtain a fluorine-containing cypress phenol intermediate, which is prepared together with polyurethane into a modified polyurethane film. Using nylon-spandex single-sided cloth, TPU hot melt adhesive, modified polyurethane film and polyester woven cloth as substrates, a nylon-spandex fabric with high waterproof performance is prepared by lamination and compounding.
[0024] The nylon-spandex fabric prepared by the present invention contains a cypress phenol antibacterial monomer, which has a good antibacterial effect. Adding it to the nylon-spandex fabric can improve the antibacterial effect of the fabric. In addition, the fluorine-containing cypress phenol intermediate prepared by the present invention has a simple preparation method and a novel structure. It contains a cypress phenol structure, and its antibacterial effect is better than that of a single cypress phenol structure, and it has been confirmed by experiments that it has a good antibacterial effect.
[0025] In addition, the fluorine-containing bishinkapol intermediate prepared by the present invention contains a large amount of fluorine elements, which have a low surface energy. When it is added to the fabric, the fluorine elements with low surface energy migrate to the surface of the material, so that the surface free energy of the material is reduced, the hydrophobicity is enhanced, and the waterproof effect is increased. In addition, the fabric prepared by the present invention has a three-layer structure and has a better waterproof effect than the fabric with a single-layer structure. The fabric prepared by the present invention has excellent antibacterial properties and waterproof effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a preparation route for fluorinated bishinkapol intermediates;
[0027] Figure 2 This is the hydrogen spectrum of the fluorinated bishinkapol intermediate; Figure 2In the H NMR spectrum, the d peak with a chemical shift of 1.05 ppm in the high-field region is the characteristic peak of four methyl groups (H-8); in the mid-field region of the spectrum, the H NMR spectrum peaks are integrated, and the ratio of the four groups of peaks is 4:12:2:4, among which the multiple peaks with a chemical shift of 3.19 ppm are the methyl signals (H-7) connected to two methyl groups respectively, the tt peak with a chemical shift of 2.45 ppm is the proton signal peak at H-12, and the other two groups of peaks (chemical shifts of 4.10 and 3.67 ppm) are the methylene proton signal peaks (H-3, 9, 10,11) connected to N atoms or O atoms; in the high-field region of the spectrum are aromatic hydrogen signals and olefinic hydrogen proton signal peaks (excluding active hydrogen proton signals), among which the peaks at chemical shifts of 5.55 and 5.41 ppm are three aromatic hydrogen proton signals (H-1, 2), and the peaks at chemical shifts of 7.17, 7.08 and 6.29 The three groups of peaks at ppm are the three olefinic hydrogen proton signals on the 7-membered ring (H-4, 5, 6); the single peak at the chemical shift of 7.66 ppm is the two hydroxyl active hydrogen proton signals (H-13); and the t peak at the chemical shift of 5.93 ppm is the NH active hydrogen proton signal (H-14). DETAILED DESCRIPTION
[0028] The flame retardant thermoplastic composition, preparation method and application of the present invention are further described below in conjunction with some specific embodiments. The specific embodiments are for further illustrating the present invention in detail, but do not limit the protection scope of the present invention.
[0029] The phase transfer catalyst is tetrabutylammonium bromide.
[0030] Example 1
[0031] (1) Add 0.4 mol of 5-chloro-metaphenylenediamine to ethanol solvent, stir and disperse, then add 1 mol of formaldehyde and 1.2 mol of cypress phenol, heat to 85°C, react for 4 h, after the reaction is completed, rotary evaporate, wash with deionized water, dry, then add ether to remove unreacted cypress phenol, separate the liquids, and rotary evaporate to obtain intermediate 1.
[0032] (2) 0.2 mol of intermediate 1 and 0.2 mol of bis(2-chloroethyl)amine were added to an ethanol solvent, stirred and dispersed, and then 80 wt % of sodium hydroxide aqueous solution was added thereto. The mixture was reacted at 90 °C for 8 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried. Then, 25% by mass of hydrochloric acid ethanol solution was added thereto for precipitation. The precipitate was collected and dried to obtain intermediate 2.
[0033] (3) 0.4 mol of intermediate 2, 0.8 mol of tridecafluorooctanol and 0.05 mol of phase transfer catalyst were added to N,N-dimethylformamide solvent, stirred and dispersed, 75 wt% sodium hydroxide aqueous solution was added thereto, and the mixture was reacted at 55°C for 24 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, allowed to stand, the organic layer was taken, washed with saturated brine, dried, and distilled under reduced pressure to obtain a fluorinated bis-hinkain phenol intermediate. The purity of the product was tested by high performance liquid chromatography, and the purity was 95.2%.
[0034] (4) Add 10 g of polyurethane and 0.5 g of fluorinated bis-hinoki phenol intermediate into N,N-dimethylformamide solvent, stir and dissolve at room temperature to obtain a casting solution, perform vacuum degassing, and scrape a 0.4 mm thick coating on a dry and clean glass plate. Immerse in deionized water for 50 h, take out, wash with deionized water, and dry to obtain a modified polyurethane film.
[0035] (5) Place a 30cm×30cm nylon-ammonia sheet on a steel plate, place the TPU hot melt adhesive in a 40-mesh steel sieve, and pass it through the steel sieve at a rate of 20g / m 2 Sprinkle TPU hot melt adhesive evenly on the surface of nylon-spandex single-sided fabric, then place modified polyurethane film on the surface of nylon-spandex single-sided fabric, and pass through a steel sieve at 20g / m 2 The TPU hot melt adhesive is evenly sprinkled on the surface of the modified polyurethane film with an amount of TPU, and then a 30cm×30cm polyester woven fabric is arranged on the surface of the modified polyurethane film. Finally, another steel plate is covered and placed in a flat vulcanizer at 80℃ and 5MPa for lamination to obtain a nylon-spandex fabric with high waterproof performance.
[0036] Example 2
[0037] (1) Add 0.4 mol of 5-chloro-metaphenylenediamine to ethanol solvent, stir and disperse, then add 1.5 mol of formaldehyde and 1 mol of cypress phenol, heat to 85°C, react for 4 h, after the reaction is completed, rotary evaporate, wash with deionized water, dry, add ether to remove unreacted cypress phenol, separate the liquids, and rotary evaporate to obtain intermediate 1.
[0038] (2) 0.2 mol of intermediate 1 and 0.3 mol of bis(2-chloroethyl)amine were added to an ethanol solvent, stirred and dispersed, and then a 70 wt % aqueous sodium hydroxide solution was added thereto. The mixture was reacted at 85° C. for 12 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried. A 25% by mass hydrochloric acid ethanol solution was then added thereto for precipitation. The precipitate was collected and dried to obtain intermediate 2.
[0039] (3) 0.4 mol of intermediate 2, 1 mol of tridecafluorooctanol and 0.04 mol of phase transfer catalyst were added to N,N-dimethylformamide solvent, stirred and dispersed, 80 wt% of sodium hydroxide aqueous solution was added thereto, and the mixture was reacted at 40°C for 30 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, allowed to stand, the organic layer was taken, washed with saturated brine, dried, and distilled under reduced pressure to obtain a fluorinated bis-hinkain phenol intermediate. The purity of the product was tested by high performance liquid chromatography, and the purity was 95.6%.
[0040] (4) Add 10 g of polyurethane and 1 g of fluorinated bis-hinoki phenol intermediate into N,N-dimethylformamide solvent, stir and dissolve at room temperature to obtain a casting solution, perform vacuum degassing, and scrape a 0.3 mm thick coating on a dry and clean glass plate. Immerse in deionized water for 72 h, take out, wash with deionized water, and dry to obtain a modified polyurethane film.
[0041] (5) Place a 30cm×30cm nylon-ammonia sheet on a steel plate, place the TPU hot melt adhesive in a 40-mesh steel sieve, and pass it through the steel sieve at a rate of 20g / m 2 Sprinkle TPU hot melt adhesive evenly on the surface of nylon-spandex single-sided fabric, then place modified polyurethane film on the surface of nylon-spandex single-sided fabric, and pass through a steel sieve at 20g / m 2 The TPU hot melt adhesive is evenly sprinkled on the surface of the modified polyurethane film with an amount of TPU, and then a 30cm×30cm polyester woven fabric is arranged on the surface of the modified polyurethane film. Finally, another steel plate is covered and placed in a flat vulcanizer at 80℃ and 5MPa for lamination to obtain a nylon-spandex fabric with high waterproof performance.
[0042] Example 3
[0043] (1) 0.4 mol of 5-chloro-m-phenylenediamine was added to an ethanol solvent and stirred to disperse. Then, 1.5 mol of formaldehyde and 0.8 mol of cypress phenol were added thereto. The temperature was raised to 80°C and the reaction was carried out for 4 h. After the reaction was completed, the mixture was rotary evaporated, washed with deionized water, and dried. Ether was then added thereto to remove the unreacted cypress phenol. The mixture was separated and rotary evaporated to obtain intermediate 1.
[0044] (2) 0.2 mol of intermediate 1 and 0.25 mol of bis(2-chloroethyl)amine were added to an ethanol solvent, stirred and dispersed, and then an 80 wt % aqueous sodium hydroxide solution was added thereto. The mixture was reacted at 95° C. for 10 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried. Then, a 25% by mass hydrochloric acid ethanol solution was added thereto for precipitation. The precipitate was collected and dried to obtain intermediate 2.
[0045] (3) 0.4 mol of intermediate 2, 0.9 mol of tridecafluorooctanol and 0.03 mol of phase transfer catalyst were added to N,N-dimethylformamide solvent, stirred and dispersed, 70 wt% sodium hydroxide aqueous solution was added thereto, and the mixture was reacted at 45°C for 20 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, allowed to stand, the organic layer was taken, washed with saturated brine, dried, and distilled under reduced pressure to obtain a fluorinated bis-hinkain phenol intermediate. The purity of the product was tested by high performance liquid chromatography, and the purity was 96.1%.
[0046] (4) Add 10 g of polyurethane and 1.5 g of fluorinated bis-hinoki phenol intermediate into N,N-dimethylformamide solvent, stir and dissolve at room temperature to obtain a casting solution, perform vacuum degassing, and scrape a 0.2 mm thick coating on a dry and clean glass plate. Immerse in deionized water for 72 h, take out, wash with deionized water, and dry to obtain a modified polyurethane film.
[0047] (5) Place a 30cm×30cm nylon-ammonia sheet on a steel plate, place the TPU hot melt adhesive in a 40-mesh steel sieve, and pass it through the steel sieve at a rate of 20g / m 2 Sprinkle TPU hot melt adhesive evenly on the surface of nylon-spandex single-sided fabric, then place modified polyurethane film on the surface of nylon-spandex single-sided fabric, and pass through a steel sieve at 20g / m 2 The TPU hot melt adhesive is evenly sprinkled on the surface of the modified polyurethane film with an amount of TPU, and then a 30cm×30cm polyester woven fabric is arranged on the surface of the modified polyurethane film. Finally, another steel plate is covered and placed in a flat vulcanizer at 80℃ and 5MPa for lamination to obtain a nylon-spandex fabric with high waterproof performance.
[0048] Example 4
[0049] (1) Add 0.4 mol of 5-chloro-metaphenylenediamine to ethanol solvent, stir and disperse, then add 1.6 mol of formaldehyde and 1 mol of cypress phenol, heat to 95°C, react for 2 h, and after the reaction, rotary evaporate, wash with deionized water, dry, add ether to remove unreacted cypress phenol, separate the liquids, and rotary evaporate to obtain intermediate 1.
[0050] (2) 0.2 mol of intermediate 1 and 0.24 mol of bis(2-chloroethyl)amine were added to an ethanol solvent, stirred and dispersed, and then a 75 wt % aqueous sodium hydroxide solution was added thereto. The mixture was reacted at 95° C. for 10 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried. A 25% by mass hydrochloric acid ethanol solution was then added thereto for precipitation. The precipitate was collected and dried to obtain intermediate 2.
[0051] (3) 0.4 mol of intermediate 2, 1 mol of tridecafluorooctanol and 0.04 mol of phase transfer catalyst were added to N,N-dimethylformamide solvent, stirred and dispersed, 80 wt% of sodium hydroxide aqueous solution was added thereto, and the mixture was reacted at 50°C for 24 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, allowed to stand, the organic layer was taken, washed with saturated brine, dried, and distilled under reduced pressure to obtain a fluorinated bis-hinkain phenol intermediate. The purity of the product was tested by high performance liquid chromatography, and the purity was 94.8%.
[0052] (4) Add 10 g of polyurethane and 2 g of fluorinated bis-hinoki phenol intermediate into N,N-dimethylformamide solvent, stir and dissolve at room temperature to obtain a casting solution, perform vacuum degassing, and scrape a 0.4 mm thick coating on a dry and clean glass plate. Immerse in deionized water for 60 h, take out, wash with deionized water, and dry to obtain a modified polyurethane film.
[0053] (5) Place a 30cm×30cm nylon-ammonia sheet on a steel plate, place the TPU hot melt adhesive in a 40-mesh steel sieve, and pass it through the steel sieve at a rate of 20g / m 2 Sprinkle TPU hot melt adhesive evenly on the surface of nylon-spandex single-sided fabric, then place modified polyurethane film on the surface of nylon-spandex single-sided fabric, and pass through a steel sieve at 20g / m 2 The TPU hot melt adhesive is evenly sprinkled on the surface of the modified polyurethane film with an amount of TPU, and then a 30cm×30cm polyester woven fabric is arranged on the surface of the modified polyurethane film. Finally, another steel plate is covered and placed in a flat vulcanizer at 80℃ and 5MPa for lamination to obtain a nylon-spandex fabric with high waterproof performance.
[0054] Example 5
[0055] (1) 0.4 mol of 5-chloro-m-phenylenediamine was added to an ethanol solvent and stirred to disperse. Then, 1 mol of formaldehyde and 1.2 mol of cypress phenol were added thereto. The temperature was raised to 85°C and the reaction was carried out for 6 h. After the reaction was completed, the mixture was rotary evaporated, washed with deionized water, and dried. Ether was then added thereto to remove the unreacted cypress phenol. The mixture was separated and rotary evaporated to obtain intermediate 1.
[0056] (2) 0.2 mol of intermediate 1 and 0.25 mol of bis(2-chloroethyl)amine were added to an ethanol solvent, stirred and dispersed, and then a 75 wt % sodium hydroxide aqueous solution was added thereto. The mixture was reacted at 90° C. for 10 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried. A 25% by mass hydrochloric acid ethanol solution was then added thereto for precipitation. The precipitate was collected and dried to obtain intermediate 2.
[0057] (3) 0.4 mol of intermediate 2, 0.9 mol of tridecafluorooctanol and 0.04 mol of phase transfer catalyst were added to N,N-dimethylformamide solvent, stirred and dispersed, 80 wt% of sodium hydroxide aqueous solution was added thereto, and the mixture was reacted at 40°C for 25 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, allowed to stand, the organic layer was taken, washed with saturated brine, dried, and distilled under reduced pressure to obtain a fluorinated bis-hinkain phenol intermediate. The purity of the product was tested by high performance liquid chromatography, and the purity was 96.5%.
[0058] (4) Add 10 g of polyurethane and 2.5 g of fluorinated bis-hinoki phenol intermediate into N,N-dimethylformamide solvent, stir and dissolve at room temperature to obtain a casting solution, perform vacuum degassing, and scrape a 0.3 mm thick coating on a dry and clean glass plate. Immerse in deionized water for 48 h, take out, wash with deionized water, and dry to obtain a modified polyurethane film.
[0059] (5) Place a 30cm×30cm nylon-ammonia sheet on a steel plate, place the TPU hot melt adhesive in a 40-mesh steel sieve, and pass it through the steel sieve at a rate of 20g / m 2 Sprinkle TPU hot melt adhesive evenly on the surface of nylon-spandex single-sided fabric, then place modified polyurethane film on the surface of nylon-spandex single-sided fabric, and pass through a steel sieve at 20g / m 2 The TPU hot melt adhesive is evenly sprinkled on the surface of the modified polyurethane film with an amount of TPU, and then a 30cm×30cm polyester woven fabric is arranged on the surface of the modified polyurethane film. Finally, another steel plate is covered and placed in a flat vulcanizer at 80℃ and 5MPa for lamination to obtain a nylon-spandex fabric with high waterproof performance.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that in step (4), intermediate 1 is used instead of the fluorinated bishinkalin intermediate.
[0062] Refer to GB / T4745-2012 and use a water tester to test the waterproof effect of the fabric.
[0063] Table 1: Test results of waterproof effect of various embodiments and comparative examples
[0064]
[0065] It can be seen from the table that the fabric prepared by the present invention has a good waterproof effect.
[0066] Refer to GB / T20944.3-2008, the test bacteria are Staphylococcus aureus and Escherichia coli, antibacterial rate (%) = (average live bacteria concentration of control fabric (CFU / mL) - average live bacteria concentration of antibacterial fabric (CFU / mL)) / average live bacteria concentration of control fabric (CFU / mL). The control fabric is nylon-spandex fabric.
[0067] Table 2: Antibacterial effect test results of each embodiment and comparative example
[0068]
[0069] It can be seen from the table that the maximum antibacterial rate of the fabric prepared by the present invention reaches 99.8% and 99.3%. According to the evaluation standard of GB / T20944.3-2008, the fabric has excellent antibacterial effect.
[0070] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a nylon-spandex fabric with high waterproof performance, characterized in that: The preparation method is as follows: Step (1), adding polyurethane and fluorinated bishinkalin intermediate to N,N-dimethylformamide solvent, stirring and dissolving at room temperature to obtain a casting solution, vacuum degassing, scraping on a dry and clean glass plate to form a coating film, immersing in deionized water, soaking for 48-72 hours, taking out, washing with deionized water, and drying to obtain a modified polyurethane film. The preparation method of the fluorinated bishinkalin intermediate is: S1, adding 5-chloro-metaphenylenediamine to an ethanol solvent, stirring and dispersing, then adding formaldehyde and cypress phenol, heating to 80-95°C, reacting for 2-6 hours, and after the reaction, rotary evaporation, washing with deionized water, drying, and purification to obtain intermediate 1; S2, adding intermediate 1 and bis(2-chloroethyl)amine to an ethanol solvent, stirring and dispersing, and then adding 70wt%-80wt% of a sodium hydroxide aqueous solution thereto, reacting at 85-95°C for 8-12h. After the reaction is completed, filtering, washing with deionized water, drying, and purifying to obtain intermediate 2; S3, adding intermediate 2, tridecafluorooctanol, and a phase transfer catalyst to N,N-dimethylformamide solvent, stirring and dispersing, adding 70wt%-80wt% sodium hydroxide aqueous solution thereto, reacting at 40-55°C for 20-30h, after the reaction is completed, cooling to room temperature, filtering, standing, taking the organic layer, washing with saturated brine, drying, and distilling under reduced pressure to obtain a fluorinated bishinkalin intermediate; Step (2), arranging the nylon-spandex single-sided fabric on a steel plate, placing the TPU hot melt adhesive in a steel sieve, and evenly sprinkling the TPU hot melt adhesive on the surface of the nylon-spandex single-sided fabric through the steel sieve, then placing a modified polyurethane film on the surface of the nylon-spandex single-sided fabric, and evenly sprinkling the TPU hot melt adhesive on the surface of the modified polyurethane film through the steel sieve, and then arranging the polyester woven on the surface of the modified polyurethane film, and finally covering another steel plate, placing it in a flat vulcanizer, and performing lamination to obtain a nylon-spandex fabric with high waterproof performance.
2. The method for preparing a nylon-spandex fabric with high waterproof performance according to claim 1, characterized in that: In the step (1), the mass ratio of polyurethane to fluorinated bishinokitiol intermediate is 100:5-25.
3. The method for preparing nylon-spandex fabric with high waterproof performance according to claim 1, characterized in that: In the step (1), the coating thickness is 0.2-0.4 mm.
4. The method for preparing nylon-spandex fabric with high waterproof performance according to claim 1, characterized in that: In step (2), the amount of TPU hot melt adhesive used is 20g / m 2 .
5. The method for preparing nylon-spandex fabric with high waterproof performance according to claim 1, characterized in that: In the step (2), the temperature of the flat vulcanizing press is 80° C. and the pressure is 5 MPa.
6. The method for preparing nylon-spandex fabric with high waterproof performance according to claim 1, characterized in that: In the S1, the molar ratio of 5-chloro-meta-phenylenediamine, formaldehyde and cypress phenol is 1:2.5-4:2-3.
7. The method for preparing nylon-spandex fabric with high waterproof performance according to claim 1, characterized in that: In the S2, the molar ratio of the intermediate 1 to bis(2-chloroethyl)amine is 1:1-1.
5.
8. The method for preparing nylon-spandex fabric with high waterproof performance according to claim 1, characterized in that: In S3, the molar ratio of the intermediate 2 to tridecafluorooctanol is 1:2-2.5.
